Antioxidant Activity of Juice of Local Cultivar Sweet Potatoes as Free Radical Scavengers of 1,1-diphenyl-2-picrylhydrazyl (DPPH) - Endah Sri Palupi; Mulyati-Sarto Mulyati-Sarto; Rarastoeti Pratiwi (Sains dan Matematika, 2012)
Sweet potatoes (Ipomoea batatas) are tuber that have high antioxidant activity. The determination of antioxidant activity based on as percentage of inhibition of free radical DPPH. The purpose of this research was to observe the activity of three local cultivars of sweet potatoes by using DPPH method and by using vitamine C as compparison. The measurement of antioxidant activity which performed on sweet potatoes juice and vitamine C with concentration 625 ppm, 1250 ppm, 2500 ppm, 5000 ppm and 10000 ppm by using free radical of DPPH 0,004% that was soluble in ethanol pa and then was measure by using spectrofotometer. Data were analyzed by using ANOVA and LSD (Î± = 0.05). The result of this research showed that the three cultivar of sweet potatoes juice have antioxidant activity and the purple sweet potatoes cultivar Biru Mangsi had the highest antioxidant activity, although lower than vitamine C. The highest of antioxidant activity were vitamine C, followed by purple sweet potatoe, yellow sweet potatoes (cultivar Kuning Madu) and white sweet potatoes (cultivar Kapasan).